Ethnopharmacological preparations used for digestive system disorders in Talassemtane National Park (North of Morocco) - Redouan, Fatima Zahrae; Yebouk, Cheikh; Crisafulli, Alessandro; Picone, Rosa Maria; Merzouki, Abderrahmane (Ethnobotany Research and Applications, 2022)
Background: The present ethnobotanical-ethnopharmacological study of plants used to treat ailments of the digestive system was carried out in the north of Morocco. The study aims to collect data on the plants used, their vernacular names, the parts used, and their modes of preparation and administration. Methods: Surveys and interviews were carried between 2014 and 2017 in Talassemtane National Park, North of Morocco. Data were collected through open semi structured interviews with the informants. A sample of 200 people aged from 20 to 60 years, including 24 herbalists and 28 traditional healers were included. Results: We identified 96 taxa belonging to 33 botanical families. With a total of 3270 use reports, we have identified 20 medicinal uses to treat 174 conditions or symptoms classified in digestive diseases according to the international classification of primary care (ICPC-2). The main families used in this pathological group are: Lamiaceae (24 species), Asteraceae (13 species), Apiaceae (11 species), Fabaceae (8 species). Most remedies are prepared as a decoction (48%), the most used parts of the plant are: leaves (29%), fruits (16%), seeds (11%) and the most common mode of administration is oral (84%). Conclusion: Knowledge of medicinal plants used to treat acute digestive system problems was common. All the local population used medicinal plants as a first choice to deal with the illness. This study represents a useful inventory to preserve and spread this knowledge. Keywords: Ethnobotanical survey; Digestive system problems; Medicinal plants; Talassemtane National Park.